Trust in Digital Era: A Study of Public Confidence in the Reliability of Peer to Peer (P2P) Lending Considering Disadvate Issues - Gusi Putu Lestara Permana; Made Sharol Bhavani (Kompartemen: Jurnal Ilmiah Akuntansi)
In the digital era, peer-to-peer lending platforms have emerged as a new means of connecting lenders and borrowers as the financial landscape continues to shift. This study is focused on investigating the effects of negative news, public confidence in peer-to-peer lending platforms, and public trust in the digital era. Questionnaires were distributed to 120 respondents in order to collect primary data for this study. The collected data will be analyzed using the SPSS software. It is expected that the research findings will be useful for educational purposes for those who plan to use the P2P lending network.